Chemometric-Assisted Spectrophotometric Method for the Simultaneous Determination of Ciprofloxacin and Doxycycline Hyclate in Pharmaceutical Formulations - Tadele Eticha; Getu Kahsay; Fitsum Asefa; Teklebrhan Hailu; Hailekiros Gebretsadik; Tesfamichael Gebretsadikan; Boovizhikannan Thangabalan (Journal of Analytical Methods in Chemistry)
Two chemometrics methods—principal component regression and partial least squares—were developed for simultaneous spectrophotometric estimation of ciprofloxacin and doxycycline hyclate in pharmaceutical dosage forms without any pretreatment. The UV spectra of both drugs were recorded at concentrations within their linear ranges between 200 and 400 nm with the intervals λ = 2 nm at 100 wavelengths in distilled water. Beer’s law was obeyed for both drugs in the concentration ranges of 1–10 μg/mL for ciprofloxacin and 5–25 μg/mL for doxycycline hyclate. Two sets of standard mixtures, 25 as a calibration set and 9 as a validation set, were prepared. The calibration models were evaluated by cross-validation and external validation over synthetic mixtures. The optimized models were successfully applied for chemometric analysis of ciprofloxacin and doxycycline hyclate in synthetic and pharmaceutical mixtures with satisfactory accuracy (recovery values from 97.50% to 101.87%) and precision (RSD < 2%).